EFFECT OF BIOLOGICAL FERTILIZER ON GROWTH AND YIELD OF SOYBEAN IN PEAT SOIL - Josti Anangga; Mulyadi Safwan; Dwi Zulfita (Jurnal Sains Pertanian Equator, 2019)
ABSTRACT This research aims to know the dose ashes best MycoVir biological fertilizer on the growth and yield soybean on peat soil. Research conducted at the Jl. Reformasi Gg. Rencana Untan Kelurahan Bansir Laut Kecamatan Pontianak Tenggara, of date of June 1, 2018 until August 21, 2018. The design used was a completely randomized design (CRD) that consists of five treatment namely, without biological fertilizer (p0), biological fertilizer ash 5 g/polybag (p1), biological fertilizer ash 15 g/polybag (p2), biological fertilizer ash 25 g/polybag (p3), and biological fertilizer ash 35 g/polybag (p4). Observation variables in this study include : root volume (cm3), plant dry weight (g), effective root nodules (bintil), plant height (cm), day to flowering (hst), number of plods of plant (buah), number of seed of plant (buah), wight of seeds of plant (g), dry wight of 100 seeds (g). Biofertilizer showed an increase in yield variables, namely the number of pods per plant, number of seeds per plant, seed weight per plant, and weight of 100 seeds per plant so that the efficiency of the MycoVir biological fertilizer was shown at a dose of 5 g / polybag. Keywords: Biological Fertilizer, Peat Soil, Soybean